National U.S. Patient and Transplant Data for Krabbe Disease - Ghabash, Gabrielle; Wilkes, Jacob; Bonkowsky, Joshua L. (Frontiers in Pediatrics, 2021)
Krabbe disease (KD) is a leukodystrophy caused by mutations in the galactosylceramidase gene. Presymptomatic hematopoietic stem cell transplantation (HSCT) is associated with improved outcomes, but most data is from single center studies. Our objective was to characterize national patterns of HSCT for KD including whether there were disparities in HSCT utilization and outcomes. We conducted a retrospective study of KD patients ≤ age 18 years from November 1, 2015, through December 31, 2019, using the U.S. Children’s Hospital Association’s Pediatric Health Information System database. We evaluated outcomes for HSCT, intensive care unit days, and mortality, comparing age, sex, race/ethnicity, rural/urban location, and median household income. We identified 91 KD patients. HSCT, performed in 32% of patients, was associated with reduced mortality, 31% versus 68% without HSCT (p <0.003). Trends included that more males than females had HSCT (39% versus 23%); more Asian and White patients had HSCT compared to Black or Hispanic patients (75%, 33%, 25%, 17%, respectively); and that patients from households with the lowest income quartile (<$25,000) had more HSCT compared to higher income quartiles (44% versus 33%, 30%, 0%). Overall, receiving HSCT was associated with reduced mortality. We noted trends in patient groups who received HSCT. Our findings suggest that disparities in receiving HSCT could affect outcomes for KD patients.